Makna Metafisis Upacara Penti: Sebagai Ucapan Syukur kepada Tuhan dalam Masyarakat Suku Kuleng Waga Mano, Manggarai Timur (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This reseacrch aims to reveal the metaphusical meaning within the Penti ceremony as a form of thanksgiving to God (Mori Kraeng) in the Kuleng Waga Tribe community, Mano Village, Easr Manggarai. The Penti ceremony is a hereditary customary rite that marks the end of the harvest season and server as a religious momentum to renew the relationship between humans, nature, ancestors, and God. From a metaphysical perspective, Penti reflects the awareness of the existential interconnectedness between creatures and the Creator, as developed in the philosophy of Aristotle and Thomas Aquinas concerning actus assendi and participatio entis. Through a qualitative approach and cultur hermeneutics, this study interprets the symbols and ritual actions of Penti as a concrete expression of the ontological relationship between sreation and the Transcendent. The result of the study show that Penti contains three main metaphysical dimensions: first, the ontological dimension regarding human awareness of existence and dependence on God; Second, the perticipatory dimension concerning the role of ancestors as a spiritual bridge between humans and God; Third, the eschatological dimension regarding the hope for the ultimate perfection of life in God. Thus, Penti not only holds cultural value but also carries profound theological and metaphysical meaning.